An expansion of well tempered gravity. Issue 3 (23rd March 2021) - Linder, Eric V.; Appleby, Stephen
Abstract: When faced with two nigh intractable problems in cosmology — how to remove the original cosmological constant problem and how to parametrize modified gravity to explain current cosmic acceleration — we can make progress by counterposing them. The well tempered solution to the cosmological constant through degenerate scalar field dynamics also relates disparate Horndeski gravity terms, making them contrapuntal. We derive the connection between the kinetic term K and braiding term G3 for shift symmetric theories (including the running Planck mass G4 ), extending previous work on monomial or binomial dependence to polynomials of arbitrary finite degree. We also exhibit an example for an infinite series expansion. This contrapuntal condition greatly reduces the number of parameters needed to test modified gravity against cosmological observations, for these "golden" theories of gravity.